Can ivermectin mass treatments eliminate onchocerciasis in Africa? - Winnen M.; Plaisier A.P; Alley E.S; Nagelkerke N.J.D; van Oortmarssen G.; Boatin B.A; Habbema J.D.F (The World Health Organization, 2002)
OBJECTIVE: To elucidate the conditions in which mass treatment with ivermectin reduces the transmission of Onchocerca volvulus sufficiently to eliminate infection from an African community. METHODS: ONCHOSIM, a microsimulation model for onchocerciasis transmission, was used to explore the implications of different treatment intervals, coverage levels and precontrol endemicities for the likelihood of elimination. FINDINGS: Simulations suggested that control strategies based exclusively on ivermectin mass treatments could eliminate onchocerciasis. The duration of treatment required to eliminate infection depended heavily on the treatment programme and precontrol endemicity. In areas with medium to high levels of infection, annual mass treatments with 65% coverage for at least 25 years were necessary. Model predictions suggested that durations exceeding 35 years would be required if there were much heterogeneity in exposure to vector bites and, consequently, wide individual variation in microfilaria counts. If the treatment interval were reduced from 12 to 6 months the time for completion of the programme could be more than halved and elimination could be accomplished in areas of hyperendemicity, provided that the effects of each treatment would be the same as with annual treatments. However, it was doubtful whether high coverage levels could be sustained long enough to achieve worldwide eradication. CONCLUSION: Elimination of onchocerciasis from most endemic foci in Africa appears to be possible. However, the requirements in terms of duration, coverage, and frequency of treatment may be prohibitive in highly endemic areas.